Smartphone-Based Application Ã¢â‚¬Å“quizizzÃ¢â‚¬Â as a Learning Media - Wibawa, Ramadhan Prasetya; Astuti, Rohana Intan; Pangestu, Bayu Aji (Fakultas Ekonomi, Universitas Negeri Semarang, 2019)
This study aims to find out the application and contribution of smartphone-based application Ã¢â‚¬Å“Ã¢â‚¬Å“quizizzÃ¢â‚¬ÂÃ¢â‚¬Â as learning media in the University of PGRI Madiun. The method used in this research is descriptive qualitative. Data analysis technique used is an interactive method, including the process of collecting data, reducing data (compiling data in patterns, categories and specific issues), presenting data (compiling data in the form of matrices, graphs, networks, certain charts) and drawing conclusions. This research was conducted at the University of PGRI Madiun. The subjects of this study were students in Accounting and Economic Education. The results showed that the usage of smartphone-based application Ã¢â‚¬Å“quizizzÃ¢â‚¬Â as learning media can make students enthusiastic in participating in learning, so students can focus and maximize the use of smartphones as a fun learning media. The concept of maximum learning will have an impact on improving student learning outcomes.